Необыкновенные приключения Карика и Вали: повесть / Я. Л. Ларри - Ларри Ян Леопольдович (Просвещение, 1990)
3-5кл Экземпляры: БС (20170804) / Инвентарный номер: РТШ48186 / Сис.шифр: Р2 / Авт.знак: Л 25 / ГРНТИ: 17 / ББК: 84(2)